Endophytic Streptomyces from honeybee hives inhibit plant and honeybee pathogens - Reichardt, Claire; Estes, David; Carlson, Caitlin M.; Currie, Cameron R.; May, Daniel S. (Frontiers in Microbiology, 2025)
Honey bees are the most common pollinator of crops worldwide. However, our reliance on honey bees to pollinate pesticide-treated monoculture crops, combined with their pest and disease susceptibility, have led honey bee populations to fluctuate in recent years. Current treatments for honey bee bacterial and fungal diseases are inadequate due to poor safety profiles and increased pathogen resistance to these treatments. There has been renewed interest in discovering natural products from actinobacteria associated with bees to use as new hive treatments; however, few studies have determined whether these microbes are truly unique to bees or part of their broader environment. We isolated actinobacteria from plant pollen and hive pollen stores and found that the isolated Streptomyces strains share many features with previously characterized endophytic Streptomyces strains. Selected Streptomyces strains were sequenced, and the genomes were used to search for phylogenetic relationships, identify genetic markers of endophytism, and compare biosynthetic gene clusters. LC-MS/MS was used to confirm the production and identities of the genetically predicted natural products. Finally, we tested the ability of the isolated actinobacteria to inhibit the growth of both plant and honey bee pathogens. Specific taxa, like Streptomyces albidoflavus and Streptomyces olivaceus, were regularly isolated from both plants and hives and produced many of the same natural products. These natural products and the Streptomyces strains that produce them may represent a starting point for antibiotics that could be used to help protect these critical pollinators.